Effect of Coffee Consumption with Muscle Strength in Male Adolescents Futsal Team - Ayu Astianing Tiyas; Eveline Margo (Jurnal Multidisiplin Madani, 2023)
In the realm of sports, caffeine has become a popular choice for athletes seeking to enhance their strength and maintain peak performance levels. Research has demonstrated that caffeine can facilitate the conversion of fat into energy and increase calcium levels within muscle cells, thereby improving muscle performance and reducing fatigue. This study was conducted to examine the impact of coffee consumption on muscle strength in a male high school futsal team. Employing an experimental method involving a one-group pre-post test design, the study included 22 teenagers. This research was conducted at SMA 5 Tambun Selatan, Bekasi. The researchers utilized the vertical jump test to gauge leg muscle strength both before and after administering coffee to participants and analysed use paired t-test. The result is increased muscle strength after giving coffee at a dose of 2mg CAF/kgBW (51.45±8.92) and 3mg CAF/kgBW (54.05±8.81) compared to before giving coffee (46.68±9.99). There is relationship between coffee consumption and increased muscle strength (p=0.00)